2024
DOI: 10.1038/s41467-024-45636-x
|View full text |Cite
|
Sign up to set email alerts
|

Dubosiella newyorkensis modulates immune tolerance in colitis via the L-lysine-activated AhR-IDO1-Kyn pathway

Yanan Zhang,
Shuyu Tu,
Xingwei Ji
et al.

Abstract: Commensal bacteria generate immensely diverse active metabolites to maintain gut homeostasis, however their fundamental role in establishing an immunotolerogenic microenvironment in the intestinal tract remains obscure. Here, we demonstrate that an understudied murine commensal bacterium, Dubosiella newyorkensis, and its human homologue Clostridium innocuum, have a probiotic immunomodulatory effect on dextran sulfate sodium-induced colitis using conventional, antibiotic-treated and germ-free mouse models. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Among the changes observed in gut microbiota, the abundance of Dubosiella newyorkensis was sharply increased in both of the sample-supplemented groups (Figure ). The beneficial effects of Dubosiella newyorkensis have been reported in some recent studies, including antiaging, modulating immune tolerance in colitis, and improving hypertension by altering bile acid metabolism . It has also been suggested as a potential probiotic to improve obesity and liver disease.…”
Section: Discussionmentioning
confidence: 97%
“…Among the changes observed in gut microbiota, the abundance of Dubosiella newyorkensis was sharply increased in both of the sample-supplemented groups (Figure ). The beneficial effects of Dubosiella newyorkensis have been reported in some recent studies, including antiaging, modulating immune tolerance in colitis, and improving hypertension by altering bile acid metabolism . It has also been suggested as a potential probiotic to improve obesity and liver disease.…”
Section: Discussionmentioning
confidence: 97%
“…Bacteroides vulgatus is one of the enriched gut microbes in mild/moderate MASLD and advanced fibrosis patients. , Its abundance was positively correlated with proinflammatory mediators including IL-6, TNF-α, insulin resistance, and obesity in multiple in vivo and in vitro studies. In the meantime, two beneficial strains, Dubosiella newyorkensis and Muribaculum intestinale, were enriched in the HFDP-E group (Figure C,D). Dubosiella newyorkensis was previously identified as a promising probiotic for its ability to produce l -lysine, which contributes to an immunosuppressive microenvironment mediated by the Treg in inflammatory bowel diseases. , Muribaculum intestinale is a newly culturable species and has been reported to decrease in abundance upon HFD feeding . In both MASLD and MASLD-MASH studies, coabundance analysis revealed that component species of Prohep, Bifidobacterium animalis, Bifidobacterium breve, Lactobacillus acidophilus, Lactobacillus plantarum, Lactobacillus rhamnosus, and Streptococcus thermophilus, contributed largely to the modulation of gut microbiota (Figures D and D).…”
Section: Discussionmentioning
confidence: 99%
“…Dubosiella newyorkensis was previously identified as a promising probiotic for its ability to produce L-lysine, which contributes to an immunosuppressive microenvironment mediated by the Treg in inflammatory bowel diseases. 31,32 Muribaculum intestinale is a newly culturable species and has been reported to decrease in abundance upon HFD feeding. 33 In both MASLD and MASLD-MASH studies, coabundance analysis revealed that component species of Prohep, Bifidobacterium animalis, Bifidobacterium breve, Lactobacillus acidophilus, Lactobacillus plantarum, Lactobacillus rhamnosus, and Streptococcus thermophilus, contributed largely to the modulation of gut microbiota (Figures 3D and 6D).…”
Section: Discussionmentioning
confidence: 99%
“…Dubosiella newyorkensis plays a crucial role in enhancing mucosal barrier integrity and regulating Treg/Th17 balance. It also alleviates host mucosal and extraintestinal inflammation by producing SCFAs (especially propionate) ( Zhang et al, 2024 ). Evidence from ESP intervention-involving experiments confirms an increase in butyrate.…”
Section: Discussionmentioning
confidence: 99%